Developing Asertive Media Based On Android - Haryani, Haryani; Fitria, Erlin (International Journal of Applied Guidance and Counseling, 2020)
This work aimed to develop asertif based on android. Research setting are at Junior High School 3 Godean. Media developed by combine any multimedia object, including text, images, audio, video, and interactive buttons. Content of media such as video to gain understanding about asertif behavior, 15 questions, and social media researcher information. Research method using research and development and alessi and trolip procedures. Research procedure including (1) research plan, (2) design, including flowcart and story board development, (3) development, including media production using code program, alpha, revise, and beta tested. Percentage tested found that content tested 75% (worthy), media tested 81,5% (very worthy). Student tested result 83,6% (very worthy).